Genetic diversity of ecuadorian cocoa from the germplasm bank of tenguel-guayas ecuador based in SNP’S (Bioagro, 2020)
The genetic diversity and structure of 80 cocoa introductions of Theobroma cacao L. Nacional variety existing in the farm “La Buseta”, Tenguel-Guayas, Ecuador, was studied. The characterization included 19 controls and the use of 96 markers of simple nucleotide polymorphisms (SNPs), in the Fluidigm EP1 system platform. The SNPs showed to be informative, with a mean content of polymorphic information of 0.289, and an average observed heterozygosity of 0.479 and expected heterozygosity of 0.378. The genetic profiles of the introductions were obtained from which 16 groups of identical introductions were identified. The identity probability analysis, including siblings (PIsib), concluded that the SNPs were enough to differentiate the introductions. The average of heterozygosity of the samples was 0.432 being higher in the group F (0.646) and lower in the group P (0.253). The Criollo and Contamana genotyping controls showed greater genetic distance than the Trinitario, Forastero and Ecuadorian Criollo controls. The maximum genetic distance between the introductions was 0.167. The results are consistent with the history of cultivation of the Nacional cacao, which over time received genetic contributions from other varieties. The present study constitutes a significant advance in the knowledge of the genetic diversity of Ecuador's Nacional cacao.
Keywords: Genetic diversity; germplasm; molecular markers; SNPs